Numereadsci: Boosting Numeracy and Science Literacy through English Resources at Pondok Pesantren in Pekalongan - Shilla, Rhischa Assabet; Riandita, Lilik; Syafi'i, Abdullah; Farhana, Zidna; Faradhillah, Nadia; Sari, Nurul Husnah Mustika; Prayogi, Arditya (International Journal of Research and Community Empowerment, 2025)
Numeracy and science literacy are essential competencies in navigating the increasingly complex global era. In this context, proficiency in English as an international language serves as a strategic advantage, enabling broader access to high-quality learning resources. This research-based community service aims to improve numeracy and science literacy among students at Pondok Pesantren in Pekalongan, by integrating English-based learning resources used service learning approach.. The program was introduced to improve students' readiness to face global challenges, focusing on strengthening their understanding of numeracy and science through English-based learning materials. This study evaluates the effectiveness of the program using statistically analyzed pretest and posttest data. The results showed an increase in mean score from pretest (5.44) to posttest (7.67), but statistical analysis showed that this increase was not significant. The normality test confirmed that the data distribution was normally distributed, which allowed the use of parametric statistical methods. The paired samples t-test showed no significant difference between pretest and posttest scores (p-value = 0.093). However, the effect size analysis showed a moderate effect (Cohen's d = 0.636, Hedges' g = 0.606), which suggested that the program made a meaningful impact, although not statistically significant. These results suggest that although the program has potential, it needs improvements such as longer duration, larger sample size, and more effective teaching methods to achieve significant results. The study concludes that integrating English literacy with numeracy and science education has the potential to prepare students for global challenges, and the program can be further developed with stronger implementation strategies.